2016
DOI: 10.4025/actasciagron.v38i4.30586
|View full text |Cite
|
Sign up to set email alerts
|

<b>Characterization of race 65 of <i>Colletotrichum lindemuthianum</i> by sequencing ITS regions

Abstract: ABSTRACT. The present work aimed characterize isolates of C. lindemuthianum race 65 from different regions in Brazil by ITS sequencing. A total of 17 isolates of race 65, collected in the states of Mato Grosso, Minas Gerais, Paraná, Santa Catarina and São Paulo, were studied. Analysis of the sequences of isolates 8, 9, 12, 14 and 15 revealed the presence of two single nucleotide polymorphisms (SNPs) in the ITS1 region at the same positions. These isolates, when analyzed together with the sequence of isolate 17… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…On the other hand, races 65 and 73 are the most frequent and widespread races in Brazil (Thomazella, Gonçalves‐Vidigal, Vidigal Filho, Nunes, & Vida, 2002a; Gonçalves‐Vidigal, Thomazella, Vidigal Filho, Kvitschal, & Elias, 2008; Pereira, Ishikawa, Pinto, & Souza, 2010; Damasceno e Silva, Souza, & Ishikawa, 2007; Xavier et al., 2018). Previous studies revealed that race 65 presented high variability in several states of Brazil (Coêlho et al., 2016; Ishikawa, Souza, & Davide, 2008; Rosada et al., 2010; Santos, Antunes, Rey, & Rossetto, 2008; Thomazella et al., 2002b). Race 9 has been reported on the African and American continents, especially in countries such as Brazil, Colombia, Peru, Mexico, Guatemala, Honduras, Costa Rica, the Dominican Republic, and Argentina (Balardin et al., 1997; Mahuku & Riascos, 2004; Nunes et al., 2013; Pastor‐Corrales et al., 1995; Souza et al., 2016).…”
Section: Discussionmentioning
confidence: 96%
“…On the other hand, races 65 and 73 are the most frequent and widespread races in Brazil (Thomazella, Gonçalves‐Vidigal, Vidigal Filho, Nunes, & Vida, 2002a; Gonçalves‐Vidigal, Thomazella, Vidigal Filho, Kvitschal, & Elias, 2008; Pereira, Ishikawa, Pinto, & Souza, 2010; Damasceno e Silva, Souza, & Ishikawa, 2007; Xavier et al., 2018). Previous studies revealed that race 65 presented high variability in several states of Brazil (Coêlho et al., 2016; Ishikawa, Souza, & Davide, 2008; Rosada et al., 2010; Santos, Antunes, Rey, & Rossetto, 2008; Thomazella et al., 2002b). Race 9 has been reported on the African and American continents, especially in countries such as Brazil, Colombia, Peru, Mexico, Guatemala, Honduras, Costa Rica, the Dominican Republic, and Argentina (Balardin et al., 1997; Mahuku & Riascos, 2004; Nunes et al., 2013; Pastor‐Corrales et al., 1995; Souza et al., 2016).…”
Section: Discussionmentioning
confidence: 96%
“…Currently, data regarding molecular variability of C. lindemuthianum patotypes is scarce, except for some races. For example, Talamini et al (2006), Davide and Souza (2009) and Coêlho et al (2016) reported the presence of molecular variability between and within isolates belonging to race 65. Another investigation also revealed pathogenic variability of races 65, 73 and 81 (Santos, Antunes, Rey & Rossetto, 2008).…”
Section: Intra-race Variability Based On Sequencing Of the Its1 58s And Its2 Regionsmentioning
confidence: 99%
“…These regions are transcribed and processed to originate the ribosomal RNA (Fungaro, 2000). Several genetic diversity studies have shown the efficiency of ITS markers to carry out homology sequence comparison in different phytopathogens (Torres, Ganal & Hemleben, 1990;Balardin, Smith & Kelly, 1999;Navajas, Lagnel, Fauvel & Moraes, 1999;Schoch et al, 2012;Coêlho et al, 2016;Martiniano-Souza et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the characterization of C. lindemuthianum races, studies at the molecular level have contributed to a better understanding of the variability of this fungus (Balardin et al., 1997; Mesquita et al., 1998). For instance, the genetic variability between and within races or isolates of C. lindemuthianum has been studying through random amplified polymorphic DNA (RAPD), sequencing of internal transcribed spacer, amplified fragment length polymorphism, and restriction fragment length polymorphism markers(Ansari et al., 2004; Balardin et al., 1997; Balardin et al., 1999; Coêlho et al., 2016; Damasceno Silva et al., 2007; Fabre et al., 1995; González et al., 1998; Mesquita et al., 1998; Sicard et al., 1997). The accessibility of genome sequences and the development of molecular technologies allowed the use of markers for marker‐assisted selection applied to ANT‐resistant cultivars (Schmutz et al., 2014).…”
Section: Introductionmentioning
confidence: 99%